(untitled) (Circe de clásicos y modernos, 2018)
Divine providence (πρόνοια τοῦ θεοῦ) in the texts of Philo of Alexandria is a philosophical or religious concept that points at the care of God for his creatures. As a first source we must consult the Timaeus to find the Platonic idea of providence sustained by the axiom that God is not the cause of evil, a principle that Philo follows in his theodicy. The Stoic philosophers took from Plato the idea of divine providence and adapted it to their own materialistic philosophy. Combining Platonic and Stoic elements Philo expresses in various places his idea of God’s providence. Philo wrote two treatises with the title On providence –probably at the end of his life–, which we will briefly discuss here. In On the Creation of the World according to Moses 171-172, Philo offers a compendium of his theology where his idea of God appears, and therefore his theory of the creation and the concept of providence. The analysis will focus on the explanation of providence in historical treatises and on the particular construction of the concept in the Hellenistic Jewish patriarchal society.